2019
DOI: 10.1109/tasc.2019.2931172
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design of the FCC-hh Dipole Circuits With Integrated CLIQ Protection System

Abstract: The Future Circular Collider (FCC-hh) project is a conceptual study whose goal is to design the successor of the Large Hadron Collider, increasing the collision energy from 14 to 100 TeV. The energy stored in the 16-T superconducting dipole magnets and the length of the sectors composing the 100-km FCC tunnel are considerably larger than those in present accelerators. This means that the energy stored in the FCC-hh dipole circuit is likely to be much higher than that in existing superconducting circuits. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Considering the results reported in the companion paper [8], which show that CLIQ can be employed to protect a string of 16 T magnets, the article makes the CLIQ system a strong candidate for the protection of the FCC-hh main dipole magnets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the results reported in the companion paper [8], which show that CLIQ can be employed to protect a string of 16 T magnets, the article makes the CLIQ system a strong candidate for the protection of the FCC-hh main dipole magnets.…”
Section: Discussionmentioning
confidence: 99%
“…Since the electrical circuit contains a large number of dipole magnets, the maximum voltage-to-ground depends on the adopted circuit layout. This aspect is discussed in the companion paper [8]. In this article, another feedback loop of Fig.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Concerning the integration of the magnet in a circuit string, a strong limitation comes from the maximum voltage to ground that one is ready to accept in case of a quench. A study performed for the FCC (Prioli et al 2019) has shown that, if a single magnet can be protected, a string of magnets can also be protected within given constraints (in particular voltage withstand levels and the time constant of the circuit) by a proper subdivision of a powering sector in multiple circuits.…”
Section: Quench Protectionmentioning
confidence: 99%